Unintended consequences of rangeland conservation structures - Mary H. Nichols; Jeremy R. Shaw; William K. Brandau (International Soil and Water Conservation Research, 2021)
By the 1930’s vast areas of the western US were severely degraded by overgrazing and erosion. In response, Congress authorized conservation work including the construction of erosion control and water storage, distribution, and conveyance structures. Thousands of structures such as check dams, water spreaders, and contour berms were built during the 1930s and 40s to control water and sediment in an attempt to restore degraded rangelands. However, across most of the western US, these soil and water conservation measures were implemented without the benefit of local hydrologic data or technical design guidance. Many of the established conservation practices had been developed for humid regions and were untested for use in semiarid areas that are characterized by highly variable rainfall and flash floods. As a result, many structures proved ineffective and were subsequently abandoned. Even in cases where structures were effective, many never received maintenance after their initial construction. Although structurally compromised, abandoned and unmaintained structures continue to alter surface runoff patterns and can greatly exacerbate erosion. Four sites in Arizona, USA were selected to characterize the multi-decadal impacts of conservation structures. Breaches have formed in 100% of contour berms (n = 67) while 96% of water spreader berms (n = 26) were compromised. Localized failures in these structures has created concentrated flow paths that reorganized routing of runoff and sediment thus transforming sheetflow regimes to concentrated flow regimes. This study emphasizes the unintended legacy impacts of soil and water conservation structures and highlights their role as a potential constraint on contemporary resource management.